Apolipoprotein E polymorphism in Kazakhstani population with Alzheimer's disease. (31st December 2021) - Kaiyrlykyzy, Aiym; Baibulatova, Aida; Olzhayev, Farkhad; Tsoy, Andrey; Davletov, Kairat; Askarova, Sholpan
Abstract: Background: Advanced age, apolipoprotein E ε4 (APOE) and gender are well‐known risk factors for Alzheimer's disease (AD). At least one copy of APOE‐ε4 is present in around 60% of AD cases (1). However, there are worldwide variations of APOE‐ε4 carriers by region and by ethnicity (2). There is no available data on distribution of APOE polymorphism among Alzheimer's patients in Kazakhstan. Thus, we assessed the apolipoprotein E allele and genotype frequencies in patients with Alzheimer's disease and compared them to normal controls. Method: We included 53 AD patients and 99 people with normal cognition recruited from city hospital in Astana, Kazakhstan. APOE genotypes were determined by Real Time PCR using TaqMan® SNP Genotyping Assays. Result: The APOE‐ε4 allele frequencies were found to be 82.7% for ε3, 1.9% for ε2, 41.5% for ε4 in AD group, and 92.9% for ε3, 8.1% for ε2 and 25.2% for ε4 in the control group. Genotype ε4/ε4 was found in 9.4% of AD patients compared to 1% in controls (p<0.005) Genotypic distribution of APOE polymorphism did not differ between gender in study group, however, APOE‐ε4 carrying status was significantly different by ethnic groups (p=0.04), where Kazakhs had 34.3% of APOE‐ε4 carriers, Russian and other ethnic groups 16.6% and 17.6% respectively. Conclusion: This is the first study of APOE polymorphism distribution in AD patients in Kazakhstan. APOE ε4 carrier frequency was similar to other Asian and Central European populations. Our findings are consistent with previous literature on the significance of the subjects' geographical region and ethnic context in the study of APOE genotypes in association with AD. Reference: 1. Riedel BC, Thompson PM, Brinton RD. Age, APOE and sex: Triad of risk of Alzheimer's disease. J Steroid Biochem Mol Biol. 2016 Jun;160:134‐47. doi: 10.1016/j.jsbmb.2016.03.012. Epub 2016 Mar 8. PMID: 26969397; PMCID: PMC4905558. 2. Crean S, Ward A, Mercaldi CJ, Collins JM, Cook MN, Baker NL, Arrighi HM. Apolipoprotein E ε4 prevalence in Alzheimer's disease patients varies across global populations: a systematic literature review and meta‐analysis. Dement Geriatr Cogn Disord. 2011;31(1):20‐30. doi: 10.1159/000321984. Epub 2010 Dec 1. PMID: 21124030.